Heat dissipation from a stationary brake disc, Part 2: CFD modelling and experimental validations. (May 2018) - Tirovic, Marko; Stevens, Kevin
Following from the analytical modelling presented in Part 1, this paper details a comprehensive computational fluid dynamics modelling of the three-dimensional flow field around, and heat dissipation from, a stationary brake disc. Four commonly used turbulence models were compared and the shear stress turbulence model was found to be most suitable for these studies. Inferior cooling of the anti-coning disc type is well known but the core cause in static conditions was only now established. The air flow exiting the lower vane channels at the inner rotor diameter changes direction and flows axially over the hat region. This axial flow acts as a blocker to the higher vane inlets, drastically reducing convective cooling from the upper half of the disc. The complexity of disc stationary cooling is further caused by the change of flow patterns during disc cooling. The above axial flow effects slowly vanish as the disc temperatures reduce. Consequently, convective heat transfer coefficients are affected by both, the change in the flow pattern and decrease in air velocities due to reduced air buoyancy as the disc cools down. As in Part 1, the special thermal rig was used to validate the computational fluid dynamics results quantitatively and qualitatively. The former used numerous thermocouples positioned strategically around the brake disc, with the latter introducing the concept of laser generated light plane combined with a smoke generator to enable flow visualisation. Predicted average heat transfer coefficients using computational fluid dynamics correlate well with the experimental values, and even two-dimensional analytical values (as presented in Part 1) reasonably closely follow the trends. The results present an important step in establishing cooling characteristics related to the electric parking brake application in commercial vehicles, with future publications detailing heat transfer from the entire brake assembly.